1994
DOI: 10.1111/j.1365-313x.1994.00429.x
|View full text |Cite
|
Sign up to set email alerts
|

Stability of transgenes and presence of N6 methyladenine DNA in transformed wheat cells

Abstract: Summary A number of stably transformed wheat cell lines were obtained using two different direct gene transfer techniques. When integration of the foreign genes was investigated in DNA samples taken at 10 months post‐selection, complicated profiles of transgene bands were observed in Southern blot analysis. Among these, a number of common bands were identified showing similar hybridization patterns between independently transformed cell lines. This type of hybridization pattern has been a common observation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1995
1995
1999
1999

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…Unequivocal demonstration of the existence of 6-methyladenine in eukaryotic nuclear DNAs, based on bulk determinations of modified bases, is lacking. If 6-methyladenine is present the levels are probably low (see Torres et al, 1992 andChen et al, 1994 for discussions). However indirect evidence, based on differential restriction enzyme sensitivities, suggest that 6-methyladenine is presentin eukaryotic genomic DNAs.…”
Section: Discussionmentioning
confidence: 97%
“…Unequivocal demonstration of the existence of 6-methyladenine in eukaryotic nuclear DNAs, based on bulk determinations of modified bases, is lacking. If 6-methyladenine is present the levels are probably low (see Torres et al, 1992 andChen et al, 1994 for discussions). However indirect evidence, based on differential restriction enzyme sensitivities, suggest that 6-methyladenine is presentin eukaryotic genomic DNAs.…”
Section: Discussionmentioning
confidence: 97%
“…This cell line also had high GUS expression (Tables 1 and 2), indicating that in this instance, the rearrangement did not affect gene function dramatically. Chen et al (1994) reported that transgenes in wheat cell lines subjected to direct DNA transfer may sometimes contain A/ 6 -methyladenine. This observation raises the possibility that transformation of an endophyte, such as a mycoplasma-like organism, occurred simultaneously with transformation of the wheat cells.…”
Section: Transient Expressionmentioning
confidence: 99%
“…That the SAR effect is not transferred from the GUS plasmid to the NPTII plasmid suggests that SARs are somehow functionally separated from the NPTll gene, but we can only speculate about actual integration patterns. Previous reports have shown that cotransformed plasmids frequently integrate near enough to one another to show tight genetic linkage (Chee and Slightom, 1992;Chen et al, 1994;Register et al, 1994;Peng et al, 1995), but few such events have been characterized on a molecular scale. It may be that asmall amount of intervening DNA, such as might be provided by plasmid vector sequences, is all that is necessary to prevent the SAR effect from acting on an adjacent plasmid.…”
Section: Lndependent Expressionmentioning
confidence: 99%
“…1a), presents a potential target for rearrangements in bacteria. Such an arrangement of a 35S repeat has been noted, during previous studies, to undergo small deletion rearrangements within Agrobacterium but the promoters remained transcriptionally active within transformed plant tissues (Chen et al 1994). Estimation of the sizes of restriction fragments of pBECKS 2000 .3, as mapped in Fig.…”
Section: Strategy For the Creation Of Co-integrative Binary Plasmidsmentioning
confidence: 58%